How Important is Environmentally Sustainable Tourism? Evidence in Indonesia from 1974-2018 Using NARDL Cointegration - Setiawati, Nadya; Pamungkas, Eksa (Jurnal Ekonomi & Studi Pembangunan, 2022)
Tourism is one of the most important sectors of the Indonesian economy because it is one of the mainstay sectors in obtaining foreign exchange, which is expected to increase economic growth. However, along with its positive impact on economic growth, the expansion of the tourism industry is also a significant contribution to rising CO2 emissions and energy consumption. This study focuses on assessing the impact of the tourism sector as proxied by the number of international tourist visits on GDP per capita and the environment as seen from CO2 emissions and total energy consumption. This study uses data covering 44 years (1974 - 2018). The Nonlinear Autoregressive Distributed Lag (NARDL) method was used in this study. The results indicate that an increase in total foreign tourist arrivals has a positive impact on real GDP per capita and total energy consumption in the short term, whereas a decrease has a beneficial effect on reducing real GDP per capita, CO2 emissions, and total energy consumption. In the long term, an increase in total international tourist arrivals is known to have a positive effect on increasing real GDP per capita, CO2 emissions, and total energy consumption; then, the decrease has a positive effect on reducing real GDP per capita and CO2 emissions. The result of this study demonstrates that an increase in total international tourist arrivals has a positive effect on short- and long-term impact on real GDP per capita and total energy consumption. There are several policy implications as a consideration of the results of this study, such as the use of carbon-neutral transportation and hybrid energy as well as tax breaks or low-cost financing opportunities to purchase and install green technology.